Perancangan Sistem Informasi Penggajian Karyawan di CV Anugerah Sukses Gemilang - Evitasari, Retno; Muthmainnah,; Kusumadiarti, Rini Suwartika (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The payroll process for CV Anugerah Sukses Gemilang employees already uses a computer but it is not optimal because it still uses Microsoft Excel in calculating salaries. This payroll process has not given maximum results because it is not effective and efficient. It is necessary to make a computer-based employee payroll system that is more optimal, it is hoped that it can provide accurate, effective, and efficient employee salary data information. The purpose of the research is to make it easier for the company in the payroll process and minimize problems that often occur. Information system designed using Microsoft Visual Studio 2010 programming language and MySQL database. The method used in developing this system is the prototype method with design tools using Flowmap, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD). The results of this employee payroll application can facilitate the calculation of employee salaries and can shorten the time in searching and matching employee data to minimize errors in the employee payroll system.
Keywords: System Information; Payroll; Microsoft Visual Studio 2010